2021
DOI: 10.1044/2021_jslhr-21-00153
|View full text |Cite
|
Sign up to set email alerts
|

Feedback and Feedforward Auditory-Motor Processes for Voice and Articulation in Parkinson's Disease

Abstract: Purpose Unexpected and sustained manipulations of auditory feedback during speech production result in “reflexive” and “adaptive” responses, which can shed light on feedback and feedforward auditory-motor control processes, respectively. Persons with Parkinson's disease (PwPD) have shown aberrant reflexive and adaptive responses, but responses appear to differ for control of vocal and articulatory features. However, these responses have not been examined for both voice and articulation in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…Meanwhile, patients in the on-medication state may rely less on sensory mechanisms due to the positive effects of levodopa on feedforward motor control. As a result, we would expect over-exaggerated compensatory responses to reflexive pitch perturbations in the off-medication state ( Liu et al, 2012 ; Chen et al, 2013 ; Huang et al, 2016 ; Mollaei et al, 2016 , 2019 ), but not in the on-medication state ( Abur et al, 2021 ), consistent with the existing literature on auditory perturbation responses in PD.…”
Section: Effects Of Pharmacological and Surgical Treatments For Pd On...supporting
confidence: 84%
See 1 more Smart Citation
“…Meanwhile, patients in the on-medication state may rely less on sensory mechanisms due to the positive effects of levodopa on feedforward motor control. As a result, we would expect over-exaggerated compensatory responses to reflexive pitch perturbations in the off-medication state ( Liu et al, 2012 ; Chen et al, 2013 ; Huang et al, 2016 ; Mollaei et al, 2016 , 2019 ), but not in the on-medication state ( Abur et al, 2021 ), consistent with the existing literature on auditory perturbation responses in PD.…”
Section: Effects Of Pharmacological and Surgical Treatments For Pd On...supporting
confidence: 84%
“…Although impaired adaptation in response to sustained perturbations of pitch and F1 have been demonstrated in PD ( Mollaei et al, 2013 ; Abur et al, 2018 ), reflexive responses to unpredicted perturbations of pitch and loudness appear to be either normal ( Abur et al, 2021 , who tested participants on medication) or larger than normal ( Liu et al, 2012 ; Chen et al, 2013 ; Huang et al, 2016 ; 2019 ; Mollaei et al, 2016 , 2019 ; these studies tested PD participants off medication). Deep brain stimulation applied to STN has been shown to normalize the pitch shift reflex, implicating the basal ganglia in the abnormally large pitch shift reflex in PD ( Behroozmand et al, 2019 ).…”
Section: Audiomotor Impairments In Pdmentioning
confidence: 91%
“…Then, a perturbation is gradually introduced during a ramp-up period (e.g., shifting F1 so that /ɛ/sounds more like /i/), followed by a hold phase where the perturbation is maintained, and finally, an after-effect phase where the perturbation is removed. Although post-adaptation effects are not often the focus of these studies, they have been observed after the removal of sensorimotor perturbations for speakers with and without dysarthria secondary to PD, particularly for F1 formant perturbations (Miller et al, 2023;Purcell & Munhall, 2006;Villacorta et al, 2007;Mollaei et al, 2013;Abur et al, 2021). For instance, Abur and colleagues (2021) investigated how speakers with and without PD adapted to F1 formant shift perturbations.…”
Section: Post-adaptation Effectsmentioning
confidence: 99%
“…In the context of speech production, such learning abilities have been well demonstrated by auditory-motor adaptation, in which participants modify their subsequent speech production after their auditory feedback is experimentally altered by shifting vowel formants (vocal tract resonances that distinguish vowels from one another) or vocal pitch. Speech auditory-motor adaptation remains a topic of great interest (see [1] for an extensive review on formant adaptation studies) and has been utilized to investigate speech motor control in both healthy (e.g., [2][3][4]) and clinical populations (e.g., cerebellar ataxia, [5]; Parkinson's disease, [6]; stuttering, [7]).…”
Section: Introductionmentioning
confidence: 99%